Team-Based Learning in US Colleges and Schools of Pharmacy - Allen, Rondall E. (American Journal of Pharmaceutical Education, 2013)
Objective. To characterize the use of team-based learning (TBL) in US colleges and schools of pharmacy, including factors that may affect implementation and perceptions of faculty members regarding the impact of TBL on educational outcomes. Methods. Respondents identified factors that inhibit or enable TBL use and its impact on student learning. Results were stratified by type of institution (public/private), class size, and TBL experience. Results. Sixty-nine of 100 faculty members (69%) representing 43 (86%) institutions responded. Major factors considered to enable TBL implementation included a single campus and student and administration buy-in. Inhibiting factors included distant campuses, faculty resistance, and lack of training. Compared with traditional lectures, TBL is perceived to enhance student engagement, improve students’ preparation for class, and promote achievement of course outcomes. In addition, TBL is perceived to be more effective than lectures at fostering learning in all 6 domains of Bloom’s Taxonomy. Conclusions. Despite potential implementation challenges, faculty members perceive that TBL improves student engagement and learning.